Younger Dryas glacier advances in the tropical Andes driven by increased precipitation - Neil F. Glasser; Stephan Harrison; Ryan Wilson; Joanne Wood; Matthew Peacey; Dylan Rood; Keir Nichols; Renato R. Colucci; Costanza Del Gobbo; Andrea Securo; J. C. Torres; Christian Riveros; et al. (Scientific Reports)
Abstract There is currently a debate about the timing and drivers of former glacier behaviour and climate change in the tropical Andes. Using 10Be dating we determined the ages of 21 boulders on moraines in the Santa Cruz Valley, Peru (∼10°S, altitudes ~ 4100 to ~ 4300 m a.s.l.). Former glacier extent is marked by a suite of nested outer lateral and terminal moraines. These moraines are dated to 11.1 ka, 11.6 ka, 11.8 ka and 12.0 ka, falling within the Younger Dryas Chronozone (YDC; ∼12.9–11.6 ka). Nine 10Be samples from the Lake Arhuaycocha catchment document a period of glacier thinning and lateral contraction between 12.0 ka and 11.8 ka. Reconstructed glacier Equilibrium Line Altitudes (ELA) at 11.0 to 12.0 ka with an area–altitude balance ratio (AABR) of 1.00-2.50 are between 4675 and 4835 m a.s.l. for the Arhuaycocha glacier, between 4692 and 4832 m a.s.l. for the Taullicocha glacier and between 4800 and 4940 m a.s.l. for the Artizon glacier. These values represent a depression of 300–400 m in elevation compared to contemporary values for the ELA. We infer that the glacier advances at this time were driven by increased precipitation and that these changes were most likely a response to seasonal changes in the position of the ITCZ.